2019
DOI: 10.1128/aac.01110-18
|View full text |Cite
|
Sign up to set email alerts
|

New Treatment Options against Carbapenem-Resistant Acinetobacter baumannii Infections

Abstract: Carbapenem-resistantAcinetobacter baumannii(CRAB) is a perilous nosocomial pathogen causing substantial morbidity and mortality. Current treatment options for CRAB are limited and suffer from pharmacokinetic limitations, such as high toxicity and low plasma levels. As a result, CRAB is declared as the top priority pathogen by the World Health Organization for the investment in new drugs. This urgent need for new therapies, in combination with faster FDA approval process, accelerated new drug development and pl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
179
1
7

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 252 publications
(199 citation statements)
references
References 97 publications
(102 reference statements)
2
179
1
7
Order By: Relevance
“…Recent studies suggest that kidney damage is more severe in patients treated with CMS than polymyxin B [27]. Further studies are needed to determine effective doses of available antibiotics that do not cause increased nephrotoxicity and prevent development of resistance until new agents active against MDR acinetobacter strains to be approved for clinical use [28].…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies suggest that kidney damage is more severe in patients treated with CMS than polymyxin B [27]. Further studies are needed to determine effective doses of available antibiotics that do not cause increased nephrotoxicity and prevent development of resistance until new agents active against MDR acinetobacter strains to be approved for clinical use [28].…”
Section: Discussionmentioning
confidence: 99%
“…117 However, the carbapenem-resistant A. baumannii complex can pose a significant treatment challenge; in recent years, this strain has been predominately treated with combinations of ampicillin-sulbactam, polymyxins, tigecycline, and aminoglycosides, but again these antibiotics have high toxicity and the associated efficacy is suboptimal. 118 Minocycline has also been considered to have efficacy in patients with carbapenem-resistant A. baumannii and is predominately used in combination with other reserve agents. 119 One study found that minocycline as monotherapy or combination therapy had a 73% clinical success rate in patients with a mean APACHE II score of 21.…”
Section: Mdr-acinetobacter Baumanniimentioning
confidence: 99%
“…121,122 While there are a few new potential therapeutic options for highly resistant A. baumannii in development, the majority are in preclinical phase or phase I studies. 118 A new tetracycline, eravacycline, that was FDA approved for complicated intraabdominal infections displays in vitro activity against carbapenem-resistant A. baumannii (►Table 1). 118,123 Eravacycline works by binding 30S bacterial ribosome inhibiting protein synthesis.…”
Section: Mdr-acinetobacter Baumanniimentioning
confidence: 99%
“…A. baumannii is the most common nosocomial pathogen that causes bloodstream infections (BSI) or ventilator-associated pneumonia (VAP) in many medical centers, particularly in Turkey (2, 5). Carbapenem resistance rates exceed 90% in some parts of the World (3). Carbapenem resistance among A. baumannii isolates in Turkey is ranged from 91% to 98% according to national health statistics (12).…”
Section: Discussionmentioning
confidence: 99%
“…Considering the prevalence of OXA-type carbapenemase activity in CRAB strains, eravacycline has been evaluated as a good treatment option (20–22). However, some type of carbapenemase activity, increased expression of the efflux pumps and the presence of tigecycline resistance are associated with increasing MIC values for eravacycline (1, 3).…”
Section: Discussionmentioning
confidence: 99%